(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione - 2. Il “Digesto Italiano” Utet - 3. I lemmi ecclesiasticistici e canonistici nel “Digesto Italiano” Utet - 4. Osservazioni conclusive. State law on religion and canon law in the “Digesto italiano” published by Utet (1884-1921). ABSTRACT: This paper aims to clarify the history of “Digesto Italiano”, a famous legal encyclopedia published by “Utet”, Italian publishing house in Turin. A special attention is given to the vocabulary words relating to the canon law and State law on religion.